The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1016/j.pharep.2017.02.023
|View full text |Cite
|
Sign up to set email alerts
|

High-dose testosterone enanthate supplementation boosts oxidative stress, but exerts little effect on the antioxidant barrier in sedentary adolescent male rat liver

Abstract: (Sub)chronic supplementation of sedentary adolescent male rats with high TE doses does not exert a lasting major effect on the liver antioxidant barrier and redox homeostasis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
16
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(22 citation statements)
references
References 43 publications
3
16
3
Order By: Relevance
“…The higher TE dose significantly lowered BW gain and LW as compared to those in TE-untreated EndTr rats, but caused no substantial shift in the LW/BW ratio (−5%, p = 0.66) and thus no apparent hepatotoxicity in EndTr rats. Earlier, we found a significantly reduced LW/BW ratio in high-dose TE-treated adolescent UTr rats (Sadowska-Krępa et al, 2017), which may have been due to the start of TE treatment at a younger age. The training was performed at an intensity that allows maximal fat oxidation (Purdom et al, 2018), and the mean BW gains were less in all three EndTr groups than in the respective UTr groups, see Sadowska-Krępa et al (2017).…”
Section: Discussionmentioning
confidence: 55%
See 3 more Smart Citations
“…The higher TE dose significantly lowered BW gain and LW as compared to those in TE-untreated EndTr rats, but caused no substantial shift in the LW/BW ratio (−5%, p = 0.66) and thus no apparent hepatotoxicity in EndTr rats. Earlier, we found a significantly reduced LW/BW ratio in high-dose TE-treated adolescent UTr rats (Sadowska-Krępa et al, 2017), which may have been due to the start of TE treatment at a younger age. The training was performed at an intensity that allows maximal fat oxidation (Purdom et al, 2018), and the mean BW gains were less in all three EndTr groups than in the respective UTr groups, see Sadowska-Krępa et al (2017).…”
Section: Discussionmentioning
confidence: 55%
“…All biochemical determinations in blood serum and liver samples, except for serum lipids that were not determined before, were performed as described earlier (Sadowska-Krępa et al, 2017). Specifically: The total serum testosterone (TT) level was assessed with a DSL-4100 Testosterone RIA Kit (Diagnostic Systems Laboratories, Webster, TX, USA).…”
Section: Assay Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Ischemic pre-conditioning and post-conditioning can induce increased expression of Hsp 27, which can protect the tissue from ischemia reperfusion injury, thus constituted an endogenous protective mechanism. Studies have reported that Hsp 27 can protect cerebral ischemia reperfusion injury (Sadowska-Krępa et al, 2017), increased Hsp 27 could reduce azithromycin-induced cardiac cell death (Kumar et al, 2016), and Hsp 27 can alleviate cerebral ischemia reperfusion injury (Mohammadi-Ostad-Kalayeh et al, 2017). This research found that, compared with the ischemic control group, Hsp 27 and Hsp 27 levels increased significantly after medication, suggesting that the protective effect of Antelope horn on cerebral ischemia reperfusion is correlated with the elevation of Hsp 27 and Hsp 70.…”
Section: Western Blot Test Resultsmentioning
confidence: 65%